THE DISTRIBUTION OF PROFITS IN THE MANDIRI REUKIH DAYAH INDRAPURI COOPERATIVE ACCORDING TO THE SYIRKAH ‘INÂN AGREEMENT - Putri, Raisha (Al-Mudharabah: Jurnal Ekonomi dan Keuangan Syariah, 2024)
Syirkah 'inan is a form of cooperation in capital, management and sharing of business results. Conceptually, this syirkah inan tends to be flexible so that it can be implemented in various partnership businesses including cooperatives, which are flexible in mandatory and voluntary savings as well as in the profit-sharing system, as implemented by the management of the Mandiri Gampong Reukih Dayah Cooperative, Indrapuri District, which is the object of this research. The problem that is the focus of the aim of this research is how to calculate the remaining business results in the form of consumer goods at the Mandiri Cooperative, Indrapuri District, the pattern of conversion of profit sharing value from SHU on consumer goods and a review of the syirkah 'inan contract regarding the distribution of the remaining business results in the form of consumer goods carried out by the management of the Mandiri Cooperative. This research uses a normative sociological approach with descriptive analytical research and data collection techniques through interviews and documentation. The results of the research are that the SHU calculations carried out by the Mandiri Cooperative are calculated every financial year, and the calculations are carried out by the Mandiri Cooperative management in a transparent and accountable manner. The distribution of SHU for members after being allocated the following year's capital and management operational costs is 60% and 40% into SHU which is converted by the Mandiri Cooperative in the form of goods based on the nominal value of the money received by members. Conversion in the form of goods is carried out to make it easier for members to obtain consumer goods more easily and cheaper because the cooperative management buys wholesale so it is cheaper than market prices. Based on a review of the syirkah inan concept, the SHU distribution system in the form of consumer goods is permissible because this pattern is the result of a mutual agreement made by fellow members, while the management only facilitates the members' wishes to make it easier to fulfill family needs in a more practical and cheaper manner. Agreement is the substance of this syirkah inan contract, because in fiqhiyyah the profits are shared based on the agreement.